A Study on Failure Rate, Reliability, and Collection Efficiency Trend of Bag Filters in a Cement Plant - Jena, Madhab C.; Mishra, Sarat K.; Moharana, Himanshu S. (Journal of Chemical Engineering Research Updates, 2023)
This thesis presents a comprehensive study on the failure rate, reliability, and collection efficiency trends of bag filters in a cement plant over 15 years. Bag filters are vital pollution control equipment used in various industries, including cement plants, to maintain environmental compliance. Understanding their performance and failure patterns is crucial to ensure efficient and reliable operation while adhering to stringent pollution control standards. The research findings reveal that the failure rate trend of bag filters closely follows the bathtub curve, with an initial high failure rate, a period of lower failures, and a subsequent increase in failures as the equipment nears the end of its life cycle. Reliability trends align with Madhab's Hat curve, exhibiting higher reliability during the first 10 to 12 years of operation, followed by a decline in reliability. The collection efficiency of bag filters declines as the equipment ages, with the efficiency decreasing from 99.998% in the early years to 95.05% in the 15th year. This emphasizes the importance of maintenance and retrofitting for older dust collection equipment to maintain high collection efficiency. The study concludes that the typical life span of bag filters ranges from 10 to 15 years, after which major maintenance interventions are necessary to minimize failure rates. The research provides valuable insights for maintenance engineers, design engineers, and reliability engineers, enabling them to improve the performance of pollution control equipment, such as bag filters, reverse air bag houses (RABH), and electrostatic precipitators (ESP), to meet the pollution control standards set by regulatory authorities.